Analisis Hukum Terhadap Keadilan Secara Musyawarah Mufakat Dalam Penyelesaian Perkara Pidana di Tingkat Kepolisian : Studi Surat Edaran Kapolri Nomor : SE/8/VIi/2018 - Nelson Syah Habibi S.; Madiasa Ablisar; Muhammad Hamdan; Marlina Marlina (Universitas Sumatera Utara, 2019)
Abstract. Law enforcement systems and methods in Indonesia show that there is a development in community justice by Restorative Justice that reflects justice as a balance of human life, so that deviant behavior from criminals is considered as an act that eliminates balance, the model of case settlement is an effort to restore that balance. Kapolri as the head of the Indonesian National Police then issues Circular Number: 8/VII/2018 concerning Restorative Justice in the Settlement of Criminal Cases, with hope to accommodate the values ​​of justice in society. The position of the Circular is a policy regulation or instructions to members of the National Police based on Law Number 2 of 2002 concerning the Indonesian National Police, it’s not part from the Legislative context that can bind the public, but manifestations of the Police's efforts in overcoming criminal acts and are expected to fulfill a sense of justice among the community by obtaining satisfactory agreement according to their wishes win-win solutions. The implementation process is at the Police level with the achievement of a peace agreement between the victim and the suspect, ending with the issuance of an order to terminate the Investigation with the reason that Restorative justice is signed by the supervisor's investigator. The criminal case that is settled in a case resolved through diversion based on the SPPA Law or case which is a complaint offense will be completed and has legal certainty, but the case with a general offense still has the opportunity to continue if the victim feels dissatisfied. The results of peace will be a consideration of the judge in giving his decision. Keywords : restorative justice, criminals case settlement, policy regulation